Question
upstudy study bank question image url

QUESTION 1 Solve for \( x \) \( \begin{array}{l}1.1 \quad x^{2}+4 x-21=0 \\ 1.2 \quad 3 x^{2}-5 x=1 \\ 1.3 \quad \sqrt{2-x}=x-2 \\ \text { QUESTION } 2 \\ 2.1 \quad x^{2}-4 x+2=0 \\ 2.2 \text { Solve for } x \text { by completing the square: } \\ \text { Given the following the equation } f(x)=5 x^{2}-12 x+4 \\ \text { Solve for } x \text { if } f(x)>0 \\ 2.3 \text { If } \frac{6}{\sqrt{2}-2}=m+n \sqrt{t} \\ \text { Determine the values of } m, n \text { and } t\end{array} \)

Ask by Nguyen Ross. in South Africa
Feb 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

- **1.1:** \( x = -7 \) or \( x = 3 \) - **1.2:** \( x = \frac{5 - \sqrt{37}}{6} \) or \( x = \frac{5 + \sqrt{37}}{6} \) - **1.3:** \( x = -\sqrt{2} + 2 \) or \( x = 2 \) - **2.1:** \( x = 2 - \sqrt{2} \) or \( x = 2 + \sqrt{2} \) - **2.2:** \( x < \frac{2}{5} \) or \( x > 2 \) - **2.3:** \( m = -6 \), \( n = -3 \), \( t = 2 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Bonus Knowledge

To solve \( x^{2}+4x-21=0 \), we can factor it as \( (x+7)(x-3)=0 \). Thus, the solutions are \( x = -7 \) and \( x = 3 \). For \( 3x^2-5x=1 \), rearranging gives \( 3x^2-5x-1=0 \). Using the quadratic formula, we find \( x = \frac{5 \pm \sqrt{25 + 12}}{6} = \frac{5 \pm \sqrt{37}}{6} \). This gives two solutions: \( x = \frac{5 + \sqrt{37}}{6} \) and \( x = \frac{5 - \sqrt{37}}{6} \). For \( \sqrt{2-x}=x-2 \), squaring both sides leads to the equation \( 2-x=(x-2)^2 \). Solving this results in \( x = \frac{2+\sqrt{10}}{2} \) and \( x = \frac{2-\sqrt{10}}{2} \) after simplifying. As for \( x^{2}-4x+2=0 \), applying the quadratic formula reveals the solutions to be \( x = 2 \pm \sqrt{2} \). In the completion of the square for \( f(x)=5x^{2}-12x+4 \), rewriting it reveals that \( f(x) > 0 \) when the resulting quadratic is greater than zero, leading to determining values at which the function is positive. Lastly, to simplify \( \frac{6}{\sqrt{2}-2} \), we multiply the numerator and denominator by \( \sqrt{2}+2 \). This yields \( m = 3(\sqrt{2}+2) \), \( n = 3 \), and \( t=2 \). For the complete analysis and exploration of how quadratics affect various real-world situations, one might want to check out some math-focused applications like projectile motion or optimization problems. If you're interested in diving deeper, I recommend exploring resources that break down the quadratic formula step-by-step or watching videos that visualize graphs of quadratic equations. They can really help solidify your understanding!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy